2021
DOI: 10.1039/d0bm01421d
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactide-co-glycolide) copolymer using zinc proline as a biocompatible initiator for irinotecan delivery to colon cancer in vivo

Abstract: Green synthesis of mPEG–PLGA and nanoformulation for delivery of irinotecan to colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…The neutropenia side effect of Ir signi cantly reduced in Ir encapsulated P-DSPE-Ir/P-DSPE-PEG-Ir nanocarriers. In the literature our previous study report m-PEG-PLGA based nanoparticles with Tween-80 and Pluronics coating successfully used for pancreatic, colon cancer delivery-PEG-PLGA based nanoparticles shown better tumor growth delay and non-immunogenicity, biocompatibility [47]. In the present study Overall results, reported synthesis of PLGA and theire characterization and further well characterized for colonic delivery applications.…”
Section: Discussionsupporting
confidence: 56%
“…The neutropenia side effect of Ir signi cantly reduced in Ir encapsulated P-DSPE-Ir/P-DSPE-PEG-Ir nanocarriers. In the literature our previous study report m-PEG-PLGA based nanoparticles with Tween-80 and Pluronics coating successfully used for pancreatic, colon cancer delivery-PEG-PLGA based nanoparticles shown better tumor growth delay and non-immunogenicity, biocompatibility [47]. In the present study Overall results, reported synthesis of PLGA and theire characterization and further well characterized for colonic delivery applications.…”
Section: Discussionsupporting
confidence: 56%
“…However, with the advent of biocompatibility and biodegradable polymers, the development of suitable polymer micellar drug delivery systems coupled with sustained drug release has made excellent carriers for antitumor drugs ( Gao et al, 2015 ; Tan L et al, 2017 ; Li et al, 2020 ; Lu et al, 2020 ; Chen et al, 2021 ). Moreover, self-assembly and passive targeting of EPR might contribute to a greater therapeutic effect ( Tan L et al, 2017 ; Lu et al, 2020 ; Li et al, 2020 ; Giram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To preserve the sink condition, 3 mL of test samples were withdrawn and replaced with fresh buffer at 0, 0.25, 0.5, 0.75, 1, 1.5, 2, 3, 4, 6, 8, 10, and 12 h. Cellulose acetate syringe filters with a pore size 0.45 µm were used to filter each sample taken. 35 The concentration of EPL in IC and NP was measured at 388 nm wavelength using a UV-Vis spectrophotometer and analyzed using DD-Solver (Microsoft Add-In) software.…”
Section: Methodsmentioning
confidence: 99%